2017
DOI: 10.1002/pi.5490
|View full text |Cite
|
Sign up to set email alerts
|

Thiol Michael addition reaction: a facile tool for introducing peptides into polymer‐based gene delivery systems

Abstract: Polymers, as widely used non-viral gene carriers, suffer from high cytotoxicity and relatively low transfection efficiency. Such crucial drawbacks of polymers could be solved by incorporating short and bioactive peptides. The resulting synthetic polymer-peptide conjugates can not only maintain their own special characteristics, but also gain novel characteristics far beyond those of their parent polymer and peptide components to overcome barriers to gene delivery. There are various chemoselective reactions app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 95 publications
(136 reference statements)
0
26
0
Order By: Relevance
“…The latter amides were treated with PCl5 and the resulting sulfonyl-chlorides were subjected to reduction with Zn/H2SO4/H2O following the standard procedures 29 to obtain thiols 4a,b in moderate yields. Cyclizations of the substituted mercapto-amides 4a,b were achieved via the thio-Michael 30 additions using Et3N as a catalyst in dry DCM to give the substituted pyrido [3,2-b][1,4]thiazepinones 5a,b. The resulting bicyclic thiazepinones were reduced with LiAlH4 in Et2O/THF to afford cyclic amines 6a,b followed by Nalkylation with ethyl α-or β-or γ-halo-alkanoate 7a-c in the presence of K2CO3 in DMF to obtain the corresponding N-ester precursors 8a-f in good overall yields.…”
Section: Resultsmentioning
confidence: 99%
“…The latter amides were treated with PCl5 and the resulting sulfonyl-chlorides were subjected to reduction with Zn/H2SO4/H2O following the standard procedures 29 to obtain thiols 4a,b in moderate yields. Cyclizations of the substituted mercapto-amides 4a,b were achieved via the thio-Michael 30 additions using Et3N as a catalyst in dry DCM to give the substituted pyrido [3,2-b][1,4]thiazepinones 5a,b. The resulting bicyclic thiazepinones were reduced with LiAlH4 in Et2O/THF to afford cyclic amines 6a,b followed by Nalkylation with ethyl α-or β-or γ-halo-alkanoate 7a-c in the presence of K2CO3 in DMF to obtain the corresponding N-ester precursors 8a-f in good overall yields.…”
Section: Resultsmentioning
confidence: 99%
“…Further functionalization of the PEI polymer is to combine the PEG stealth technology with the use of ligands and Abs (scFv or full Abs) for the active-targeting delivery though a hetero-bifunctional crosslinker such as α-maleimide-ω-N-hydroxysuccinimide ester polyethylene glycol (Mal-PEG-NHS ester) [ 79 , 80 ]. Thiol–ene click reaction including thiol–ene radical and thiol Michael addition reaction is one of the most commonly used methods for preparing peptide–polymer conjugates [ 81 ]. In the current study, the maleimide of MAL-PEG-NHS can react with a free thiol group of cysteine residue of MSLN scFv by the Michael addition reaction, while the NHS can react with the primary amine of the PEI-LGA polymer.…”
Section: Discussionmentioning
confidence: 99%
“…The thiol-Michael addition reaction characterized by the conjugate addition of a thiol to a Michael acceptor has been widely used in bioconjugation and materials chemistry. 117,118 In 2014, Hemantha et al reported the generation of monoUb-and diUb-a-globin using thiol-Michael addition (Fig. 14A).…”
Section: Chemical Ubiquitination Using Conjugate Additionmentioning
confidence: 99%